Steuerung der Landnutzung durch Raumplanung: Instrumente und Kooperationsprobleme zwischen Landwirtschaft und Naturschutz - Kathrin Exler (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2002)
– Managing the Use of Land by Means of Regional Planning: Instruments and Collaboration Problems between the Farming Community and Nature ConservationAfter describing a series of plans with implications for land use, this study aims to examine the collaboration problems which exist between the main groups involved and elaborate on potential legal solutions. Main results are the following:1. German law requires that the interests of the farming community and nature conservation are taken into account in the overall consideration of planning decisions. Any specialist plans already available - bearing in mind the different procedures existing between the various federal states - must also be integrated into the planning process. 2. If farming interests or the interests of nature conservation and countryside protection cannot be asserted in the overall planning process as laid down by the law, the decisions are in many cases political and, as such, cannot be dealt with by legal means. In legal terms, the interests are already recognised as having equal status.3. The rivalry frequently encountered between the farming community and nature conservation over the use of land mostly occurs when the land is intended to be used for other purposes (i.e. for housing development, infrastructure etc.). The necessity for conservation-related compensation creates a relationship of tension which in many cases is not directly attributable to nature conservation and farming. An example is the low amount of conservation-related compensation when viewed in comparison with a housing development project.4. The law only partially regulates the coordination of nature-preservation and agrarian specialist planning. However, both sides - the farming community (consideration of high-yielding land) and conservation (upgrading the chances of realising landscape planning) have an equal interest in seeing coordinated measures implemented at an early stage. In practice, an adequate procedure has already been developed. In legal terms, however, it is difficult to register and cope with the possibilities and problems associated with the informal methods of coordination.5. Ultimately, the success of the coordination and collaboration depends largely on the commitment shown by the parties involved. However, the coordination of regional planning instruments at an early stage does not solve the problems of acceptance between the farming community and nature conservation as long as the realisation of legal conservationist measures are financially unattractive for farmers or could even jeopardise their existence.
Keywords: 330; Agrarboden; Naturschutz; Regionalplanung; Raumordnung; Deutschland